ANALISIS KONTRIBUSI PAJAK DAERAH TERHADAP PENERIMAAN PENDAPATAN ASLI DAERAH (Studi Kasus Pada Badan Pendapatan, Pengelolaan Keuangan dan Aset Daerah Wilayah Eks-Karesidenan Surakarta) - Azizah, Laila Nur; Harimurti, Fadjar; Kristianto, Djoko (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
This research aims to find out the contribution of Local Tax and its effecton Local Indigenous Income. The dependent variable used in this study wasRegional Native Income. While the independent variables are Hotel Tax,Restaurant Tax, Billboard Tax and Parking Tax. The population in this study isthe Budget Realization Report of Budget Realization Report (LRA) of SragenRegency, Karanganyar Regency, Sukoharjo Regency, Wonogiri Regency, KlatenRegency, Boyolali Regency and Surakarta City in 2014 – 2018. Samplingtechniques (saturated samples). The analysis used in this study is to use multiplelinear contribution and regression analyses.Based on the calculation of contribution analysis during 2014-2018 it canbe said that, Hotel Tax in Former Surakarta Regency is very less contributing tothe Local Original Income. Based on the calculation can be said that, theRestaurant Tax in The Former Surakarta Regency is very less contributing to theLocal Original Income. Based on the calculation can be said that, Rekalme Tax inFormer Surakarta Regency is very less contributing to The Local OriginalIncome. Based on the calculation can be said that, Parking Tax in FormerSurakarta Regency is very less contributing to The Local Original Income. Basedon the partial spss test results of the Hotel Tax, the Restaurant Tax and BillboardTax have no effect while the Parking Tax affects the Local Original Income.Meanwhile, the hotel tax, restaurant tax, billboard tax and parking tax togetheraffect the original income of the area in the former Surakarta Regency.